Tubular Heads in Bacteriophages from Lactic Streptococci - Chopin, Marie-Christine (1983)
Tubular bacteriophage heads were observed in the lysate of two phages from Streptococcus lactis obtained from single plaques without mutagenesis. The frequency of appearance of the tubular heads was 2.5 and 16%.